Digital Transformation, Sharia Compliance, and Customer Loyalty in Islamic Banking: A Systematic Literature Review - Jumarni Jumarni; Andi Farhami Lahila M; Siradjuddin Siradjuddin; Andi Nurrahma Gaffar; Siti Nur Reskiyawati Said (Jurnal Administrasi Bisnis, 2026)
This study aims to systematically review the literature on digital transformation, sharia compliance, and customer loyalty in Islamic banking. The development of digital services such as mobile banking, internet banking, e-banking, and electronic service quality has changed the way Islamic banks interact with their customers. At the same time, Islamic banking has distinctive characteristics because customer loyalty is not only influenced by digital service quality, but also by sharia compliance, religiosity, trust, and sharia governance. This study employs a systematic literature review approach by analyzing 27 articles related to digital banking, Islamic mobile banking, e-service quality, sharia compliance, religiosity, trust, satisfaction, and customer loyalty. The findings show that e-service quality and mobile banking service quality are the most dominant digital transformation factors in shaping customer satisfaction and loyalty. Meanwhile, sharia compliance, religiosity, Islamic trust, halal banking attitude, and Sharia governance play important roles in building customer trust, satisfaction, and loyalty in Islamic banking. The findings also indicate that customer satisfaction and e-satisfaction are the most dominant mediating variables, while trust is important but does not always directly influence loyalty. This study proposes an integrative conceptual framework that positions digital transformation and sharia compliance as two main foundations for customer loyalty formation in Islamic banking. Future research is suggested to develop the concepts of digital sharia compliance and Islamic digital trust in the context of Islamic digital banking services.